Perception of medical teachers towards undergraduate medical theoretical assessment system in a medical college of West Bengal - Adhikari, Anjan; Bhattacharya, Sangita; Indu, Rania; Ray, Moumita; Waghmare, Lalit (International Journal of Research in Medical Sciences, 2017)
Background: With change of disease pattern and complexities of therapy globally, medical education become challenging. Problem based learning and self-directed learning became more relevant and occupied its space in medical education. Assessment is very crucial with the change in curriculum for appropriate feedback and learning in the system. Present study evaluated the perception of medical teachers on this issue of theory examination. Assessment or evaluation plays a pivotal role in effectivity of the system. Assessors always guide any system to achieve its objectives. Methods: This is an observational study, done with a questionnaire. It was done by interviewing the faculties of R.G. Kar Medical College, Kolkata, West Bengal who were examiners at University level. Results: Present study comprised faculty of fifteen undergraduate Departments of R. G. Kar Medical College, Kolkata 29.68% faculty supported semester system. 70.32% faculty participated as the study population. 48.4% agreed and 35.93% strongly agreed on the concept of model answers. A majority of the faculties (31.25%) strongly agreed on the issue that answers should be checked by two or more examiners. Regarding the threshold of pass marks, 48.4% strongly agreed and 43.75% agreed that students need to get 50% marks separately in theory examination to get through the examination. Conclusions: Present study evaluated importance of theory assessment system in medical education. It also necessitates further research to improve the objectivity of theory assessment system in medical curriculum at University level, in India.